(untitled) (American International Journal of Economics and Finance Research, 2019)
The paper examined the implications of tax revenue on economy growth in Nigeria. The specific objective of this study is to examine the relationship between tax revenue and gross domestic product in Nigeria. Simple Regression was used to achieve the objective of this study. Secondary data will be sourced from International Monetary Fund’s Government Finance Statistics. It was revealed that there was a weak correlation between dependent and independent variable. It was also discovered that there was no significant relationship between tax revenue and gross domestic product in Nigeria. The study therefore recommends that Government should formulate policies that will minimize the volume of tax leakages in order to increase total tax revenue that will contribute positively to economic growth in Nigeria. The study also recommends that Government should always make sure that tax revenue is spent on social amenities and welfares of the Nigerian citizens.